G115(P) Acceptability of hypnotherapy as a treatment option for habit cough. (12th March 2018) - Prathivadi Bhayankaram, N; Gilchrist, FJ; Samuels, M
Abstract : Aims: Cough is a common cause of morbidity in childhood and can have a significant impact on the quality of life of a child and their family. Habit cough is a non-organic cough which occurs during the day but ceases during sleep. There is no established consensus on managing habit cough, but studies in North America have suggested hypnotherapy as a treatment option. We conducted a study to determine the acceptability of this treatment for habit cough. Methods: We conducted a service evaluation where a trained play specialist offered hypnotherapy sessions to children diagnosed with habit cough. A paediatrics trainee conducted semi-structured interviews with parents of patients who underwent hypnotherapy between January 2015 and September 2016. Interviews were recorded, transcribed and analysed for common themes. Results: Nine patients underwent hypnotherapy during our service evaluation period and all nine parents were contacted. Cough was the only symptom in 7 patients, but one patient had a more complex motor tic disorder and one patient had severe anxiety. The habit cough had been present for between four months and three years. All nine parents stated that they found hypnotherapy an acceptable and appropriate treatment option. Four were pleasantly surprised after initially being sceptical. Most parents were unsure what to expect and commented that they were pleased it had worked and would like to have further sessions or similar alternatives in future. After hypnotherapy, parents reported a significant reduction in cough in 6/9 (67%) children. This included complete cough cessation in 4/9 (44%). The parents of 5 children (56%) stated that after hypnotherapy, cough was no longer affecting their child's or the family's quality of life, even despite the absence of complete cough cessation. Conclusion: This is the first study exploring the use of hypnotherapy for habit cough outside of North America. Parents found hypnotherapy to be an acceptable treatment option, and furthermore, it seems to be effective in reducing morbidity and cough cessation in some cases. A future randomised control trial would determine the efficacy of hypnotherapy in treating habit cough.